SAT0444 Facilitators and barriers for good clinical practice in RA and OA: The eumusc.net study. (23rd January 2014) - Moe, R.H.; Woolf, A.D.; Stoffer, M.; Petersson, I.F.; Uhlig, T.
Abstract : Background: EUMUSC.net is a European project supported by the EU, EULAR and 24 partners across Europe with the purpose of improving musculoskeletal care in Europe. So far, EUMUSC.net has established an information network, the impact of musculoskeltal conditions across Europe, Standards of Care (SOC) and Health Care Quality Indicators (HCQI). There is evidence that recommendations for clinical practice in rheumatic diseases are not being followed as intended 1;2 . Preliminary SOC for people with osteoarthritis and rheumatoid arthritis with related HCQI for the provision of care applicable for different European health care settings in treating people with osteoarthritis and rheumatoid arthritis have been developed during the EUMUSC.net project and need to be validated by patients and health professionals in different health care settings. Objectives: The current part of the EUMUSC project examines facilitators and barriers for implementing the SOC and HCQI in health care systems across the European countries. Methods: Questionnaires addressing agreement, feasibility and applicability of SOC will be widely distributed among patients, health care professionals, and policy makers throughout Europe. Information in depth will also be collected through focus group interviews among patients and health care professionals. Results: 11 OA and 16 RA SOC with related HCQI have been identified during the EUMUSC.net project. We currently examine facilitators and barriers on the levels of knowledge, attitude and behaviour for the implementations of SOC. For this purpose questionnaires with selected SOC and HCQI collect experiences on what supports or hinders the application of good clinical practice among patients, health care professionals, and policy makers throughout Europe. Further, a focus group is being assembled with rheumatology health care professionals and patients to get deeper insight into what facilitates and inhibits the implementation of SOC in different European countries. Finally, examples of good practice will be sought to inspire improved health care in rheumatic diseases. Results will also be available on the website www.EUMUSC.net . Conclusions: Standards of care in OA and RA are subject to facilitators and barriers in different European countries. Equity in health care provision can only be achieved by enhancing facilitators and overcoming modifiable barriers across Europe. References: Mazieres B, Scmidely N, Hauselmann HJ, Martin-Mola E, Serni U, Verbruggen AA et al. Level of acceptability of EULAR recommendations for the management of knee osteoarthritis by practitioners in different European countries. Ann.Rheum.Dis. 2005;64:1158-64. Chevalier X, Marre JP, de BJ, Hercek A. Questionnaire survey of management and prescription of general practitioners in knee osteoarthritis: a comparison with 2000 EULAR recommendations. Clin.Exp.Rheumatol. 2004;22:205-12. Disclosure of Interest: None Declared